Predicting fatigue crack growth life for cold-worked holes based on existing closed-form residual stress models. - Wang, Z.; Zhang, Xiang (Elsevier Science B.V., Amsterdam., 2003)
This paper studies the capability of four closed-form solutions for calculating cold expansion-induced residual stresses. The aim is to check whether these models are able to provide accurate solutions of residual stresses for three aerospace grade aluminium alloys of medium thickness so that fatigue life can be estimated using these residual stress models without going to the formidable finite element analysis. Based on these studies, crack growth lives for three different kinds of specimens are predicted by the AFGROW computer program and compared with experimental tests. Factors affecting the capability of these closed-form solutions are examined, and modifications to these models based on the fatigue tests and parametric studies are suggested. The study demonstrates that good prediction of crack growth life can be obtained if a suitable closed- form model is used.